Electrophysiological approach to determine kinetic parameters of sucrose uptake by single sieve elements or phloem parenchyma cells in intact Vicia faba plants - Hafke, Jens B.; Höll, Sabina-Roxana; Kühn, Christina; Van Bel, Aart J. (Frontiers in Plant Science, 2013)
Apart from a few using cut aphid stylets, no attempts have been made thus far to measure in vivo sucrose-uptake properties of sieve elements. We investigated the kinetics of sucrose uptake by single sieve elements and phloem parenchyma cells in Vicia faba plants. To this end, microelectrodes were inserted into free-lying phloem cells in the main vein of the youngest fully-expanded leaf, half-way along the stem, in the transition zone between the autotrophic and heterotrophic part of the stem, and in the root axis. A top-to-bottom membrane potential gradient of sieve elements was observed along the stem (-130 mV to -110 mV), while the membrane potential of the phloem parenchyma cells was stable (approx. -100 mV). In roots, the membrane potential of sieve elements dropped abruptly to -55 mV. Bathing solutions having various sucrose concentrations were administered and sucrose/H+-induced depolarisations were recorded. Data analysis by nonlinear least-square data fittings as well as by linear Eadie-Hofstee (EH) -transformations pointed at biphasic Michaelis-Menten kinetics (2 MM, EH: Km1 1.2-1.8 mM, Km2 6.6-9.0 mM) of sucrose uptake by sieve elements. However, Akaike’s Information Criterion (AIC) favoured single MM kinetics. Using single MM as the best-fitting model, Km values for sucrose uptake by sieve elements decreased along the plant axis from 1 to 7 mM. For phloem parenchyma cells, higher Km values (EH: Km1 10 mM, Km2 70 mM) as compared to sieve elements were found. In preliminary patch-clamp experiments with sieve-element protoplasts, small sucrose-coupled proton currents (-0.1 to -0.3 pA/ pF) were detected in the whole-cell mode. In conclusion (a) Km values for sucrose uptake measured by electrophysiology are similar to those obtained with heterologous systems, (b) electrophysiology provides a useful tool for in-situ determination of Km values, (c) As yet, it remains unclear if one or two uptake systems are involved in sucrose uptake by sieve elements, (d) Affin